Diagnose da composição nutricional e eficiência de fertilizantes nitrogenados na cultura do milho - Modesto, Viviane Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The nitrogen fertilization is the agricultural practice that influences the most the grains yield in the maize culture. Together to the use of technologies the use of fertilizers promotes a better use of N by the cultures. This way, it was aimed evaluate the biometric characteristics, chlorophyll amount, biomass production, and the nutritional status of maize plants when submitted to different sources and doses of nitrogenous fertilizers. The experiment was carried out in a Luvisol, at Embrapa/CNPC Experimental Field in Sobral, CE, Brazil. The treatments were five nitrogen sources: urea + NBPT, urea + polymer, urea + enzymatic inhibitor, urea + sulfur covering, and urea without technology added. Three doses of nitrogen were used: 45, 67,5 and 90 kg N ha-1 and an additional treatment, without nitrogen fertilization, as top dressing 30 days after planting. The nitrogen fertilization combined to technology promoted higher chlorophyll contents and biomass production in the maize plants. The maximum agronomic economic efficiency was reached using urea without nitrogen fertilization, as top dressing 30 days after planting. The nitrogen fertilization combined to technology promoted higher chlorophyll contents and biomass production in the maize plants. The maximum agronomic economic efficiency was reached using urea without technology added, urea + urease inhibitor, and urea + elementary sulfur

A adubação nitrogenada é a prática agrícola que mais influencia o rendimento de grãos na cultura do milho e, o uso de fertilizantes com tecnologias agregadas promove o melhor aproveitamento do N pelas culturas. Assim, objetivou-se avaliar as características biométricas, os teores de clorofila, a produção de biomassa e o estado nutricional de plantas de milho, submetidas à aplicação de diferentes fontes e doses de fertilizantes nitrogenados. O ensaio foi conduzido em um Luvissolo, no campo experimental da Embrapa/CNPC, em Sobral-CE. Os tratamentos consistiram de cinco fontes de nitrogênio: uréia + NBPT; uréia + polímero; uréia + inibidor enzimático; uréia + capeamento com enxofre; e, uréia sem tecnologia agregada. Foram usadas três doses: 45; 67,5 e 90 kg de N ha-1 e um tratamento adicional sem adubação nitrogenada, aplicadas em cobertura 30 dias após a semeadura. A utilização de fertilizantes nitrogenados com tecnologias agregadas promoveu maiores teores de clorofila e produção de biomassa das plantas de milho. A máxima eficiência agronômica foi alcançada empregando-se uréia sem tecnologia agregada, uréia + inibidor enzimático e, uréia + enxofre elementar
Keywords: Milho - Nutrição; Adubos e fertilizantes; Fertilizantes nitrogenados; Biometria; Fisiologia vegetal; Nitrogen fertilizers